Production potential and profitability of some rice (Oryza sativa)-based cropping systems involving sequence cropping of pulses and oilseeds in rice fallows - PRATIBHA, G; PILLAI, K G; SATYANARAYANA, V (The Indian Journal of Agricultural Sciences, 2013)
A field experiment was carried out at Hyderabad during 1990-91 and 1991-92 to develop and test suitable rice (Oryza sativa L.)-based cropping system and also appropriate tillage practice for some upland crops grown after rice. Groundnut (Arachis hypogaea L.), blackgram (Phaseolus mungo L.), sunflower (Helianthus annuus L.) and castor (Ricinuscommunis L.) were used as the test crops with different tillage practices, viz tillage, ploughing twice with country plough,ploughing with bullock-drawn mouldboard plough and disc harrowing, ploughing with tractor-drawn mouldboard ploughonce and disc harrowing, working cultivator twice, and ploughing with tractor-drawn mouldboard plough once androtovator twice. Land preparation with tractor-drawn mouldboard plough once and rotary tiller twice recorded higher net return and benefit: cost ratio. The net returns of different crops were in the order: grountnut> sunflower> blackgram > castor. However, rice--blackgram sequence registered higher production efficiency, and rice-castor gave higher land- utilization efficiency. Rice-groundnut sequence proved more sustainable and profitable, especially for Telangana region of Andhra Pradesh.